2014
DOI: 10.1590/s0100-39842014000100018
|View full text |Cite
|
Sign up to set email alerts
|

Lithium nephropathy: a case report

Abstract: Although widely used in the management of bipolar disorder, lithium may cause adverse kidney effects. The importance of the present study is to report the case of a 59-year-old woman who was under regular treatment with lithium for bipolar disorder and whose imaging studies demonstrated the presence of multiple renal microcysts, suggesting lithium nephropathy as main diagnostic hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Although lithium‐induced side effects have been previously well documented, clinical studies have shown that diagnosis of lithium nephropathy is uncommon. A retrospective study revealed that 85% of patients in 14 studies did not demonstrate signs of renal failure and only 0.37% had altered histopathological analysis . The ultrasound changes seen as a result of lithium‐induced nephropathy are also uncommon, having only been reported in a few patients with prolonged lithium therapy (>20 years) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lithium‐induced side effects have been previously well documented, clinical studies have shown that diagnosis of lithium nephropathy is uncommon. A retrospective study revealed that 85% of patients in 14 studies did not demonstrate signs of renal failure and only 0.37% had altered histopathological analysis . The ultrasound changes seen as a result of lithium‐induced nephropathy are also uncommon, having only been reported in a few patients with prolonged lithium therapy (>20 years) …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study revealed that 85% of patients in 14 studies did not demonstrate signs of renal failure and only 0.37% had altered histopathological analysis. 3 The ultrasound changes seen as a result of lithium-induced nephropathy are also uncommon, having only been reported in a few patients with prolonged lithium therapy (>20 years). 1 A study by Di Salvo et al 4 described that lithium-induced tubulointerstitial nephritis is characterised histologically by distal tubular microcysts and interstitial fibrosis.…”
Section: Case Descriptionmentioning
confidence: 99%